Research progress of anxiety and depression in patients with systemic lupus erythematosus (系统性红斑狼疮患者焦虑抑郁的相关影响因素研究进展) - MA Haiyan (马海燕); WANG Xia (王霞); ZHANG Lijuan (张利娟); WAN Qin (万青) (中西医结合护理)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with multiple systemic lesions. It has a high incidence of anxiety and depression due to the prolonged course of the disease, which adversely affects the treatment, affects the quality of life of patients, and threatens the life and health of patients. Through searching and reading relevant literature, the research status of anxiety and depression, influencing factors and psychological intervention measures were summarized to guide clinical timely discovery of relevant factors and psychological intervention, so as to reduce the incidence of anxiety and depression in SLE patients and improve their quality of life. (系统性红斑狼疮(SLE)是一种具有多系统损害表现的慢性自身免疫病, 病程迁延不愈, 患者易产生焦虑抑郁的负性情绪, 不利于治疗, 且影响患者生活质量, 甚至威胁患者生命健康。疾病活动度、患者的经济水平、婚姻状况、文化程度、应对方式、社会支持以及治疗方式等均可能影响SLE患者心理情绪, 临床应做到早识别早干预, 评估风险人群, 针对高风险患者积极开展心理干预, 提高心理弹性, 降低SLE患者焦虑抑郁发生率, 提高其生活质量。)